ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA KPRI IKHLAS KANTOR KEMENTERIAN AGAMA KOTA SURAKARTA - Muhammad Rofiq Sunarko, Erny Widyastuti, Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
This research is a case study on KPRI Ikhlas Kantor Kementerian Agama KotaSurakarta, in the years 2011 â€“ 2015 using quantitative analysis. The study aims toanalyze the level of financial performance KPRI Ikhlas in terms of liquidity, solvencyratios, profitability ratios, and the ratio of the activity. Liquidity analysis carried outby the current ratio technique; solvency ratio using the total debt to total assetsratio; profitability ratio using return on assets ratio, and receivable turnover ratiomeasured activity. The conclusion of this study is the liquidity ratio is rated â€œnot verygoodâ€, the profitability ratio classified as â€œnot goodâ€, while the solvency ratio andthe ratio of activity classified as â€œgoodâ€.Keywords: financial ratios, financial performance.